Seminar on Nanotechnology and Entomology - Ruiz Cancino, Enrique; Universidad Autónoma de Tamaulipas (Libros UAT, 2019)
Science is moving towards new directions and in different directions. One of them is the development of Nanotechnology, based on scientific discoveries that began more than five decades ago but that even in this century are beginning to give concrete results.  It is important to note that the behavior of the elements is different from myel nano, presenting other properties that can be used in the development of various products, in many fields of industry.  "Nature can teach us a lot about Nanotechnology," said Professor Zhongfan Liu. Insects are an inexhaustible source of resources for different scientific areas. They are already being researched for the development of nanobots and to develop new products or to improve others, based on some of their structures although only some species of butterflies, moths, flies, beetles, chicharras and cockroaches have been used. There are more than one million described species of insects, so much remains to be done and discovered. Current applications are already present in communications, clothing, sporting goods, vehicles and other household products. In the near future they will be used for human and animal health, in agriculture and in almost any field of knowledge. Therefore, the Academic Body of Applied Entomology of the Autonomous University of Tamaulipas, together with the CA of Nanostructured Materials of the Institute of Physics and the CA of Agricultural Production of the Faculty of Agronomy of the UASLP, organized a Seminar on Nanotechnology and Entomology in November 2009 to present the progress made in these fields.